2011
DOI: 10.1007/s13197-011-0543-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of reaction parameters of acidolysis reaction between mustard oil and capric acid by using Thermomyces lanuginosus lipase

Abstract: Structured lipids were prepared from mustard oil by enzymatic acidolysis reaction with capric acid (C10) using lipase enzyme TLIM from Thermomyces lanuginosus as biocatalyst. Parameters such as substrate molar ratio, enzyme concentration, reaction temperature, stirring speed and time of maximum incorporation, were studied for the optimization of the reaction. The optimized set of process conditions was predicted by response surface methodology (RSM) and genetic algorithm (GA). The robustness of GA and RSM was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Khodadadi et al ( 43 ) also reported that Lipozyme TL IM and Novozyme 435 were more effective in transesterification reaction between flaxseed oil and tricaprylin than Lipozyme RM IM and Amano DF. Table 1 ( 44 , 48 - 53 ) summarizes the utilization of immobilized lipase for MLM lipase synthesis.…”
Section: Enzymes For Mlm Structured Lipid Synthesis: Types Ans Sourcesmentioning
confidence: 99%
“…Khodadadi et al ( 43 ) also reported that Lipozyme TL IM and Novozyme 435 were more effective in transesterification reaction between flaxseed oil and tricaprylin than Lipozyme RM IM and Amano DF. Table 1 ( 44 , 48 - 53 ) summarizes the utilization of immobilized lipase for MLM lipase synthesis.…”
Section: Enzymes For Mlm Structured Lipid Synthesis: Types Ans Sourcesmentioning
confidence: 99%
“…Many of recent studies have produced MLM‐type MLCTs from diverse kinds of plant oils (mainly soybean, corn, olive, canola, rice bran, avocado, mustard, borage, echium, and pine nut oils and palm olein) and MCFAs, such as caprylic (8:0) and capric acids (10:0). These published studies employed free or immobilized sn ‐1,3‐specific lipases developed in laboratories of Kim and others (), Nunes and others (), Ifeduba and Akoh (), and Qin and others (), as well as commercial immobilized sn ‐1,3‐specific lipases, such as Lipozyme RM IM and Lipozyme TL IM (Jennings and others ; Ozturk and others ; Sengupta and Ghosh ; Chnadhapuram and Sunkireddy ; Choi and others ; Savaghebi and others ; Wang and others ; Gokce and others ; Caballero and others ; Silroy and others ). In particular, the use of PBRs is preferred in the enzymatic preparation of MLM‐type MLCTs because rupture of the supporting materials for immobilized lipases, which facilitates acyl migration that causes the formation of other types of MLCT species can be avoided in these reactors (Xu ).…”
Section: Mlctsmentioning
confidence: 99%
“…Batch Reactor STBR MCFA capric, caprylic and lauric and mustard oil were taken in 3:1 molar ratio and stirred at 200 rpm at 60 for different time periods with 10 of three different lipozyme enzymes 2 . The total volume of the substrate was 100 ml.…”
Section: Production Of Mcfa Rich Mustard Oil By Stirred Tankmentioning
confidence: 99%
“…Medium chain fatty acids MCFA rich mustard oil was prepared in our previous study by enzymatic acidolysis reaction using Thermomyces lanuginosus lipase as biocatalyst 2 . We thought about MCFA because triglycerides containing MCFA ie.…”
Section: Introductionmentioning
confidence: 99%